Pengembangan Sistem Penyediaan Air Bersih Pedesaan di Desa Wai U, Kecamatan Mangoli Tengah, Kabupaten Kepulauan Sula, Provinsi Maluku Utara - Arno Adi Kuntoro; Resanti Audrienne; Rofidzias Siswo Wicaksono; Almira Abdul Kholik; Vicky Candra Purnama; Fahrul Kedafota; Widodo Widodo; Salsa Alfadhila Permana; Mohammad Farid; M. Bagus Adityawan; Widyaningtias Widyaningtias; Ana Nurganah Chaidar (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Wai U Village has a problem with the limited capacity of the village's clean water supply system. This community service activity aims to retrofit the existing clean water supply system, which previously experienced technical problems, and to increase the capacity of the existing system. The implementation method consists of pre-site visit interviews, field surveys, geoelectric surveys to determine aquifer potential, and water quality laboratory tests for drinking water standards. The results of the geoelectric data analysis show that the potential aquifer was located at 30m below the surface. The water quality test results show that the groundwater quality generally meets the class-1 water quality standards for drinking water. Field survey activities were followed by the construction of groundwater wells, water towers, water reservoirs, pumps, and a series of pipes connecting the new water sources to the existing pipe distribution network of Wai U Village. The final result of this activity was the improvement of the clean water supply capacity in Wai U Village, which was able to connect houses that previously depended on water sources from dug wells. There are 69 houses in the Wai U Village. Before experiencing technical problems, the existing water supply system (Pamsimas) in Wai U Village was connected to 38 houses (55%). The construction of new water supply infrastructure was connected to the remaining 31 houses (45%); thus, this activity has succeeded in increasing clean water network connections by almost 100% in Wai U Village. However, several house connections require rehabilitation. This activity is expected to be one of the real contributions of universities to achieving water, food, and energy security in Wai U Village, which is categorized as a 3T region.